P53 abnormalities in adenocarcinoma of the gastric cardia and antrum. Issue 5 (1st October 1999) - Fléjou, J F; Gratio, V; Muzeau, F; Hamelin, R
Abstract : AIM: To compare the frequency and type of p53 alterations (gene mutation and/or protein overexpression) in a consecutive series of surgically resected adenocarcinomas arising in the gastric cardia and gastric antrum, and to evaluate associations with clinicopathological findings (age, sex, and tumour histology, grade, and stage). METHODS: The series comprised 50 patients with adenocarcinoma of the cardia and 20 patients with adenocarcinoma of the antrum. p53 gene mutations (exons 5-8) were detected by denaturing gradient gel analysis and DNA sequencing. Nuclear p53 overexpression was detected by immunohistochemistry with the DO7 antibody. RESULTS: p53 gene mutations were found in 21 of 50 and five of 20 adenocarcinomas of the cardia and the antrum, respectively. Base transitions occurring at CpG dinucleotides were frequent in both types of tumour. p53 protein overexpression was seen in 32 of 50 and seven of 20 adenocarcinomas of the cardia and of the antrum, respectively. p53 gene mutation and/or protein overexpression were significantly more frequent in adenocarcinomas of the cardia (37 of 50) than in adenocarcinomas of the antrum (seven of 20). There were no differences in the clinicopathological characteristics of the tumours between p53 positive and p53 negative cases in both types of cancer. CONCLUSIONS: This study shows that p53 alterations are more frequent in adenocarcinoma of the cardia than in adenocarcinoma of the antrum. This feature is consistent with the clinical and epidemiological characteristics of these cancers, which suggest that adenocarcinoma arising in the gastric cardia might be related to oesophageal adenocarcinoma, and unrelated to adenocarcinomas of the gastric body and antrum.